2000
DOI: 10.1128/mcb.20.10.3705-3714.2000
|View full text |Cite
|
Sign up to set email alerts
|

p53-Mediated DNA Repair Responses to UV Radiation: Studies of Mouse Cells Lacking p53, p21, and/orgadd45 Genes

Abstract: Human cells lacking functional p53 exhibit a partial deficiency in nucleotide excision repair (NER), the pathway for repair of UV-induced DNA damage. The global genomic repair (GGR) subpathway of NER, but not transcription-coupled repair (TCR), is mainly affected by p53 loss or inactivation. We have utilized mouse embryo fibroblasts (MEFs) lacking p53 genes or downstream effector genes of the p53 pathway, gadd45 (Gadd45a) or p21 (Cdkn1a), as well as MEFs lacking both gadd45 and p21 genes to address the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
247
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 391 publications
(265 citation statements)
references
References 38 publications
(87 reference statements)
16
247
0
2
Order By: Relevance
“…GADD45B and GADD45G are members of the GADD45 family of proteins that are induced by genotoxic stresses and various apoptotic cytokines [11][12][13] and are involved in cell cycle arrest, [14][15][16][17][18][19] DNA repair, [20][21][22] cell survival, [22][23][24][25][26][27] and apoptosis. These functions are mediated by proliferating cell nuclear antigen (PCNA), cell division control 2 (CDC2), cyclin B1 (CCNB1), and cyclin-dependent kinase inhibitor 1A (CDKN1A; also known as p21), which are classified in the GO "cell cycle" category.…”
Section: Molecularmentioning
confidence: 99%
See 1 more Smart Citation
“…GADD45B and GADD45G are members of the GADD45 family of proteins that are induced by genotoxic stresses and various apoptotic cytokines [11][12][13] and are involved in cell cycle arrest, [14][15][16][17][18][19] DNA repair, [20][21][22] cell survival, [22][23][24][25][26][27] and apoptosis. These functions are mediated by proliferating cell nuclear antigen (PCNA), cell division control 2 (CDC2), cyclin B1 (CCNB1), and cyclin-dependent kinase inhibitor 1A (CDKN1A; also known as p21), which are classified in the GO "cell cycle" category.…”
Section: Molecularmentioning
confidence: 99%
“…PCNA is involved in DNA repair and the transition from the G1 to the S phase of the cell cycle. [20][21][22] In contrast, CDKN1A inhibits PCNA and blocks the transition from the G1 to the S phase of the cell cycle. 20,38 The CDC2-CCNB1 complex is required for the transition from the G2 to the M phase.…”
Section: Molecularmentioning
confidence: 99%
“…Using gadd45 KO MEFs (24) and RKO cells expressing antisense gadd45 RNA in clonogenic survival assays, has shown that deficiency of gadd45 increases the sensitivity of cells to killing by UV irradiation or cisplatin (25). Recently, Gadd45b has been suggested to play a role in TNFa-NF-kB mediated cell survival (26), and to mediate the protective effects of CD40 co-stimulation against Fas-induced apoptosis (37).…”
Section: Gadd45 Proteins Have Been Implicated In Cycle Arrestmentioning
confidence: 99%
“…Recently, Gadd45b has been suggested to play a role in TNFa-NF-kB mediated cell survival (26), and to mediate the protective effects of CD40 co-stimulation against Fas-induced apoptosis (37). The role Gadd45 proteins play in DNA repair (11,(23)(24) is compatible with a survival function.…”
Section: Gadd45 Proteins Have Been Implicated In Cycle Arrestmentioning
confidence: 99%
“…Inherited mutations in DNA repair enzymes can increase the incidence of these tumors, and p53 alterations have also been reported. 13,14 We previously documented DNA copy number alterations in a cohort of 10 snap-frozen conjunctival squamous cell carcinoma tumor specimens and two in situ carcinomas by array-based comparative genomic hybridization assay, which allowed us to determine the most frequent DNA gains and losses. 15 We now compare transcriptional profiles of nine of these tumor specimens from a single center in Saudi Arabia to normal conjunctiva in order to identify dysregulated mRNAs representing molecular targets potentially useful for diagnosis and/or therapy.…”
mentioning
confidence: 99%